HBO’s Black Women Artist Biopics: The Josephine Baker Story and Introducing Dorothy Dandridge - Hélène Charlery (Revue LISA)
This paper analyses cable television HBO’s 1990s biopics based on the life stories of the African American dancer and singer Josephine Baker (The Josephine Baker Story, Brian Gibson, 1991) and the actress Dorothy Dandridge (Introducing Dorothy Dandridge, Martha Coolidge, 1999), demonstrating that the films articulate the network’s commercial strategy, using the life stories of African American icons to tap into a niche market. While pointing at the artists’ personal struggles, the biopics enhance the narrative power of the female voices, and yet frame them within the controlling power of white male characters. Both films deviate from the victimizing approach that often prevails in female biopics and testify to innovative narrative methods.